Biochars from animal wastes as alternative materials to treat colored effluents containing basic red 9. Issue 6 (December 2019) - Côrtes, L.N.; Druzian, S.P.; Streit, A.F.M.; Godinho, M.; Perondi, D.; Collazzo, G.C.; Oliveira, M.L.S.; Cadaval, T.R. S.; Dotto, G.L.
Highlights: Bovine bones and fish scales were pyrolyzed. The biochars were effective adsorbents for BR9 dye. Adsorption capacities of 50 mg g −1 and dye removal of 90% were obtained. Palmitic acid and imidazolidinedione were found in the pyrolytic oil. Abstract: Bovine bones (BB) and fish scales (FS) were used as alternative precursors to produce biochars, which in turn, were applied for the removal of Basic Red 9 (BR9) from aqueous solutions. BB and FS were pyrolyzed generating a solid (biochars), a liquid (pyrolytic oils) and a gas fraction. All fractions were characterized to evaluate the pyrolysis process. The biochars presented different functional groups and a mesoporous structure with surface areas around 90 m 2  g −1 . Both biochars demonstrated potential to adsorb BR9, with maximum adsorption capacities of 49.5 (BB–biochar) and 52.3 mg g –1 (FS–biochar). Pyrolytic oils were composed mainly by palmitic acid (BB) and imidazolidinedione (FS), which are compounds with biological and antioxidant activity. Pyrolysis of BB generated CO2 while pyrolysis of FS generated H2 . In summary, bovine bones and fish scales are promising precursors to concomitantly produce biochars with great adsorbent potential and oils with interesting characteristics.